Opportunities for higher education institutions to develop sustainable food systems in Africa - Pretorius, Beulah; Schönfeldt, Hettie Carina (Frontiers in Sustainable Food Systems, 2023)
An African Vice-Chancellors' Regional Food Systems Dialogue was hosted with the aim to provide a multi-stakeholder platform for stakeholders to explore various existing and emerging approaches that have the potential to deliver sustainable solutions at scale and encourage collaborative actions to directly transform Africa's agriculture and food systems. Various food system experts and leaders from policy research institutions, universities, and other stakeholders participated. A lack of coherent linkages among stakeholders, youth restlessness, and silos within and between higher education institutions were some of the challenges identified to hindering the much needed transformation. Poor links with ministries and political red tape, inadequate programme funding and capital for coping with rising input costs, as well as unsustainable resource mobilization were also reported as having a negative effect. To address these, stakeholders must embrace collaboration and transdisciplinary practices, mobilize resources, and harness partnerships for greater leverage. In addition, a systems-thinking approach to dealing with complex issues should be adopted, while partners co-design and co-create research initiatives. Information and Communications Technology (ICT) and Big Data were identified as key enablers that can ensure relevant research with appropriate translation into practice while maintaining quality and excellence. This research—together with society-relevant curriculums with emphasis on agricultural sciences and practical on-farm skills—must inform policies and practice. Higher education institutions must be committed to driving the sustainable food system transformation agenda in partnership with other stakeholders. Institutions must be at the forefront of reimagining the sector's role when it comes to transdisciplinary knowledge co-creation aimed at strengthening the continent's agro-food systems.